Interleukin-6 receptor in spindle-shaped stromal cells, a prognostic determinant of early breast cancer - Labovsky, Vivian (2016)
Spindle-shaped stromal cells, like carcinoma-associated fibroblasts and mesenchymal stem cells, influence tumor behavior and can serve as parameters in the clinical diagnosis, therapy, and prognosis of early breast cancer. Therefore, the aim of this study is to explore the clinicopathological significance of tumor necrosis factor-related apoptosis-induced ligand (TRAIL) receptors (Rs) 2 and 4 (TRAIL-R2 and R4), and interleukin-6 R (IL-6R) in spindle-shaped stromal cells, not associated with the vasculature, as prognostic determinants of early breast cancer patients. Receptors are able to trigger the migratory activity, among other functions, of these stromal cells. We conducted immunohistochemical analysis for the expression of these receptors in spindle-shaped stromal cells, not associated with the vasculature, of primary tumors from early invasive breast cancer patients, and analyzed their association with clinicopathological characteristics. Here, we demonstrate that the elevated levels of TRAIL-R2, TRAIL-R4, and IL-6R in these stromal cells were significantly associated with a higher risk of metastatic occurrence (p = 0.034, 0.026, and 0.006; respectively). Moreover, high expression of TRAIL-R4 was associated with shorter disease-free survival and metastasis-free survival (p = 0.013 and 0.019; respectively). Also, high expression of IL-6R was associated with shorter disease-free survival, metastasis-free survival, and overall survival (p = 0.003, 0.001, and 0.003; respectively). Multivariate analysis showed that IL-6R expression was an independent prognostic factor for disease-free survival and metastasis-free survival (p = 0.035). This study is the first to demonstrate that high levels of IL-6R expression in spindle-shaped stromal cells, not associated with the vasculature, could be used to identify early breast cancer patients with poor outcomes.